99.1k views
2 votes
Which equation is true?

-
A. (6 + 2) + 7 = 6 + (2 + 7)
B. (6 - 2) - 7 = 6 - (2 - 7)
C. (6 - 2) + 7 = 6 - (2 + 7)
D. (6 = 2) = 7 = 6 - 12 = 7)

User Sfrench
by
4.6k points

2 Answers

7 votes

Answer:

A.

Step-by-step explanation:

A. 15 = 15 (true)

B. -3 = 11 (false)

C. 11 = -3 (false)

User Jerrod Horton
by
4.6k points
7 votes

Answer:

(6 + 2) + 7 = 6 + (2 + 7)

Step-by-step explanation:

(6 + 2) + 7

6 + 2 = 8

8 + 7 = 15

6 + (2 + 7)

2 + 7 = 9

9 + 6 = 15

15 = 15

You will be adding 6, 2 and 7 no matter what. The parenthesis do not make a difference. 6 + 2 + 7 is the same thing as 6 + 2 + 7. 15 = 15.

User U Rogel
by
5.4k points